Implementasi Pendekatan Teaching at the Right Level dalam Meningkatkan Hasil Belajar Siswa SDN Jemur Wonosari 1 Surabaya - Ikma Qusnul Nazila; Akhwani Akhwani; Sianah Sianah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
The research conducted by researchers, namely classroom action research (PTK), aims to determine the application of the Teaching at The Right Level (TaRL) approach to increasing students' understanding of length measurement material using non-standard units. Data collection techniques are observation and tests. The test was carried out 3 times consisting of pre-cycle, cycle 1 and cycle 2. The method used in this research was simple  statistics  and  observation  sheets.  The  subjects  of  this  research  were  class  IA students at SDN Jemur Wonosari 1 Surabaya with a total of 28 students. The application of  the  TaRL  approach  to  class  IA  mathematics  subjects  at  SDN  Jemur  Wonosari  I Surabaya can be said to be successful. This is based on the results of observations of educators' activities in cycle I, namely 74%, then in cycle II it was 92%. Then, the results of observing student activities in cycle 1 were 78%, then increased to 90% in cycle 2. Apart from that, the increase in learning outcomes for class IA students at SDN Jemur Wonosari 1 Surabaya experienced a significant increase starting from pre-cycle which was 25 % then in cycle 1 it was 64% and increased in cycle 2 to 89%.